2017
DOI: 10.2147/tcrm.s140618
|View full text |Cite
|
Sign up to set email alerts
|

Are adipocytokines inflammatory or metabolic mediators in patients with inflammatory bowel disease?

Abstract: This study examined the adiponectin and leptin levels and insulin resistance (IR) in patients with inflammatory bowel disease (IBD) and the associations between these factors and IBD characteristics. Fasting serum leptin, adiponectin, glucose, and insulin levels, as well as inflammatory parameters, were measured in 105 patients with IBD (49 patients with Crohn’s disease [CD], 56 patients with ulcerative colitis [UC]) and 98 healthy controls [HC]. IR was evaluated using the Homeostatic Model Assessment of Insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…A similar observation was made by Tuzun et al, who found elevated levels of leptin in patients in the acute stage of UC [135]. In another study, Kahraman and colleagues [136] showed that leptin levels were much lower in patients with UC and CD than in healthy controls. In contrast, Karmiris et al [137] observed that serum levels of leptin were reduced in patients with IBD.…”
Section: Leptinsupporting
confidence: 75%
See 1 more Smart Citation
“…A similar observation was made by Tuzun et al, who found elevated levels of leptin in patients in the acute stage of UC [135]. In another study, Kahraman and colleagues [136] showed that leptin levels were much lower in patients with UC and CD than in healthy controls. In contrast, Karmiris et al [137] observed that serum levels of leptin were reduced in patients with IBD.…”
Section: Leptinsupporting
confidence: 75%
“…Similar to leptin, the data concerning APN serum levels in patients with IBD is controversial. For instance, Kahraman et al [136] find that, unlike in other studies, serum APN concentrations are decreased in both UC and CD patients. Similarly, Valentini et al [140] demonstrated that APN serum levels are decreased in active and inactive disease in both CD and UC individuals.…”
Section: Adiponectinmentioning
confidence: 70%
“…In this framework, the overall objective of our study was to investigate the involvement of adipose tissue-derived hormones, immune- and neuromodulatory factors in the alterations of the s-IP in D-IBS patients categorised as having normal [D-IBS(−)] or increased s-IP [D-IBS(+)] by using the lactulose/mannitol (La/Ma) ratio and healthy subjects. In particular, the aims of the study were to (a) analyse the symptom profile in D-IBS patients using a validated questionnaire, such as the Gastrointestinal Symptom Rating Scale (GSRS), in relation to whether or not there are alterations in s-IP [15] and (b) assess the circulating levels of the adipo(cyto)kines interleukin 6 (IL-6), interleukin 8 (IL-8), and tumor necrosis factor alpha (TNF- α ) that play a role as mediators of inflammation and immune activation [16], along with circulating levels of lipopolysaccharide (LPS) and toll-like receptor 4 (TLR-4), as markers of endotoxemia; leptin and adiponectin as mediators of intestinal inflammation [17]; neurotensin, with its role in preserving gut barrier integrity [18]; and the metabotropic brain-derived neurotrophic factor (BDNF), a neuroendocrine factor expressed in adipose tissue [19]. Lastly, the familial aggregation suggests a genetic component as having a role in increasing the risk of developing the pathology, although the functional role of allelic variants in IBS is still an open field [20].…”
Section: Introductionmentioning
confidence: 99%
“…Results regarding adiponectin involvement in IBD pathogenesis are also divergent 12,23 . This adipokine is characterized by anti-inflammatory properties and its concentration decreases in obesity 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is an adipokine secreted by adipocytes which stimulates the production of pro-inflammatory IL-1β and IL-6 in T cells 11 . Adiponectin is secreted from adipocytes and displays anti-inflammatory properties 12 . On the other hand, resistin is an adipokine upregulated in the mesenteric adipose tissue from CDpatients 11 which may act as an independent predictor of disease in CD 13 .…”
Section: Introductionmentioning
confidence: 99%